Urokinase – type Plasminogen Activator System in Human Breast Cancer - Al-Jubouri, Reyadh; Al-Rawi, Faeza; Al-Khafaji, Ali (Iraqi Journal of Science, 2024)
Urokinase plasminogen activator (uPA), urokinase plasminogen activator receptor (uPAR) and plasminogen activator inhibitor-1(PAI-1) are essential for metastasis, and overexpression of these molecules is strongly correlated with poor prognosis in a variety of malignant tumors. This study revealed direct correlation between immunohistochemical expression of uPA with pathological stage. No significant association of immunohistochemical expressions of uPA, uPAR and PAI-1 with immunohistochemical expressions for estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor -2 (HER-2/neu), and direct association between immunohistochemical expressions of (uPA and uPAR) as well as between immunohistochemical expressions of (uPA and PAI-1).